Analysis of the Snowball Throwing Learning Model Assisted by Canva Media on Social Studies Learning Outcomes - Erni, Erni; Haliadi, Haliadi; Hasdin, Hasdin (Journal of Education Method and Learning Strategy, 2024)
Education in the era of globalization   This   is   very important thing   in prepare Quality Human Resources​​ To use ensure sustainability development something nation. Formulation problem How application of the Snowball Throwing learning model, How How to use Canva media results Study students ' eyes social studies lesson in class IV, Is it There is the influence of the Snowball Throwing learning model assisted by Canva media on results studying social studies in Class IV of SDN 2 Bahonsuai. Research purposes Analyze the influence of the assisted Snowball Throwing learning model canva to results Study student eye social studies lessons in class IV of SDN 2 Bahonsuai. Types of research This is quantitative. Study quantitative can interpreted as method research based on philosophy​ positivism, used For research on populations or sample certain. Population and sample This aimed at 2 different classes as object study experiment. Research results Reliability test results refers to the extent of a test can produce consistent and reliable results​​​ from time to time.